(untitled) - Trammell, Sam; 1971-; Colter, Mike; 1976-; Zarvos, Marcelo; Hoy, Maysie; 1968-; Smith, Joyce; (Author at FaithWords (Firm)).; Popovic, Zoran; Staab, Rebecca; Haysbert, Dennis; et al. (Twentieth Century Fox Home Entertainment, 2019)
Based on the inspirational true story of one mothers unfaltering love in the face of impossible odds. When Joyce Smiths adopted son John falls through an icy Missouri lake, all hope seems lost. But as John lies lifeless, Joyce refuses to give up. Her steadfast belief inspires those around her to continue to pray for Johns recovery, even in the face of every case history and scientific prediction. A reminder that faith and love can create a mountain of hope, and sometimes even a miracle.
Keywords: Smith, Joyce; (Author at FaithWords (Firm)); Drama; Near-death experiences; Drama; Mothers and sons; Drama; Accidents; Drama; Faith; Drama; Missouri; Social life and customs; 21st century; Drama; Melodramas (Motion pictures); Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Fiction films; Feature films; Religious films; Film adaptations